Internalization Of Qur'anic Values In The Islamic Multicultural Education System - Mukh Nursikin; Muhammad Aji Nugroho (Didaktika Religia, 2021)
Islamic education is an Islamic institution focusing on forming human beings who have noble traits, such as good personality and behaviors according to Al-Qur’an values as life dogma on theological, norms, cultural, social, political, and economic aspects as knowledgeable, mature, humanist, and virtuous human beings. The purpose of this research is to understand comprehensively how the internalization of Al-Qur’an values in the Islamic education system at State Islamic High School (MAN) of Semarang Regency, Central Java. The method used is qualitative. Meanwhile, the data were collected with observation, in-depth interviews, and documentation. The data obtained in this study were then followed by stages, namely description, data reduction, data selection, data analysis, discussion, and conclusions. The results showed that, the internalization of Al-Qur’an values in the Islamic education system at MAN Semarang Regency, Central Java is to form the Al-Qur’an spirit. Consist in exemplary values (uswatun hasanah) in the framework of religious activities in Islamic boarding schools, discipline in various activities both in learning activities and in their dailylives, creating a conducive atmosphere in the school. Integration and internalization of Islamic values in the school coaching and problem solving for students, educators, and educational staff. While the efforts to internalize the Al-Qur’an values are, (1) The guidance conducted by the head of the madrasah regularly every Friday (2) the application of deliberation, fairness, honesty, and responsibility to the madrasah community (3) The enthusiasm of the madrasah community on implementing and obeying the madrasah regulations and avoiding detrimental actions. Madrasah as morality workshop emphasizes the habituation in behavior that illustrates the Al-Qur’an values and the goodness that students must have and become a habit of in their daily lives with a madrasah monitoring program involving various elements.